Building Resilience and Attachment in Vulnerable Adolescents (BRAVA): a brief group intervention for adolescents with mild‐to‐moderate suicidal ideation and their caregivers. Issue 4 (8th September 2021) - Cloutier, Paula; Gray, Clare; Sheridan, Nicole; Silverman, Aaron; Cappelli, Mario; Zemek, Roger; Jabbour, Mona; Reid, Sarah; Kennedy, Allison
Abstract : Introduction: Suicidal Ideation (SI) is common in adolescents and increases the risk of completed suicide. Few brief interventions have been shown to reduce SI in adolescents. The objective of this study was to evaluate the feasibility of a novel brief group intervention, building resilience and attachment in vulnerable adolescents (BRAVA), designed for adolescents and their caregivers to reduce adolescent SI. Methods: The study was a pre–post, noncontrolled trial in which 46 adolescents were enrolled in the BRAVA intervention. Adolescents and caregivers completed an intake assessment, six BRAVA group sessions, and an exit assessment 1‐week post‐BRAVA. Results: Adolescents' SI decreased significantly after completing the BRAVA treatment (pre–post difference = 18.1, 95% CI = 10.01–26.12). Significant improvements in associated symptoms of depression, anxiety, and perceived stress were also observed. Caregivers had reduced perceived stress (pre–post difference = 2.7, 95% CI = 0.30–5.16) and reduction in attachment avoidance (difference = 1.6, 95% CI = 0.29–2.91). Treatment satisfaction was high across the six modules. The rolling entry feature of the intervention allowed participants to begin treatment approximately 2 weeks sooner compared to waiting for the next group cycle. Conclusions: Study results demonstrate that the BRAVA intervention has the potential to reduce SI among adolescents who present to hospital services in crisis. Further studies are required to establish BRAVA's efficacy in a randomized controlled trial.